Eco industrial Development: As a Way of Enhancing Sustainable Development - Sertyesilisik, Begum; Sertyesilisik, Egemen (Journal of Economic Development, Environment and People, 2016)
The world’s habitat is being deteriorated especially due to the unsustainable production. The need for sustainable development and reducing humanities’ environmental footprint have been addressed in various international frameworks, meetings and reports (e.g. Kyoto protocol, the Resource Efficiency and Cleaner Production Program, the Ten Year Framework of Programs on Sustainable Consumption and Production, the UN Resource Panel, and the Green Economy Initiative, Rio+20, green building certificates, “UNEP Green Economy” in 2011, “Green New Deal” in 2012, the Intergovernmental Panel on Climate Change’s report etc.). EIDs (the eco industrial development) can act as catalysts in sustainable development and in reducing environmental footprint of the production processes. Based on an in-depth literature review, this paper aims to analyze how EID can be supported so that environmental footprint of the production processes can be reduced contributing sustainable development. With this aim, the objectives include: analysis of the need for the EID; need for the sustainable development enhanced by sustainable production and sustainable products; key success factors for, barriers against and drivers for the EID. The policy makers, companies, and researchers are expected to get benefit from this paper.